Exploring Scientific Literacy of Chemistry Education Pre-Service Teachers Through Socio-Scientific Issues Approach - Jajang Muhariyansah; Atik Rahmawati; Anita Fibonacci; Fajar Naqsyahbandi (Jurnal Tadris Kimiya, 2021)
Scientific literacy is an ability that must be had by pre-service teachers. This research aimed to find out the scientific literacy's ability of pre-service teachers in chemistry education. This research was descriptive with quantitative approach. Participants were taken by simple random sampling techniques, the participants are chemistry education students. The data source comes from scientific literacy tests with socio-scientific issues and open-ended question description tests. The validity of the data was tested using a data triangulation technique, in which researchers compare data obtained through test instruments and interview results. The results of the data analysis showed the scientific literacy of chemistry education students was dominant in the nominal and functional categories with a percentage of 33.2% and 24.2%, conceptual and multidimensional categories 13.7%; 4.4%; and 24.5% of students did not give answers the tests.